2018
DOI: 10.3390/su10051445
|View full text |Cite
|
Sign up to set email alerts
|

The Development Perspectives of Sustainable Management Accounting in Central and Eastern European Countries

Abstract: Central and Eastern European countries undergo many political, structural, social and economic changes, with growing public awareness of the need for corporate sustainability among them. These changes influence all business activities of companies; the management accounting system, however, is particularly susceptible to the effects of these changes. Management accounting research is usually carried out using a conventional, mainstream approach, followed by most scientific researchers analyzing management acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 62 publications
(85 reference statements)
2
33
0
2
Order By: Relevance
“…As Lewin [113], the founder of social psychology, indicated "there's nothing so practical as good theory", we draw from our theoretical model ( Figure 3) some important managerial implications, particularly for small business leaders in Thailand and possibly elsewhere in Asia who hope to improve their corporate sustainability by adopting the Sufficiency Economy philosophy. Based on the theoretical model, an example of sustainability management plan, as informed by Armenia et al [114], Markwick & Fill [115] and Zyznarska-Dworczak [116], is developed and demonstrated in Table 5 below. The plan contains objectives, responsible units, expected results and measures of success.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…As Lewin [113], the founder of social psychology, indicated "there's nothing so practical as good theory", we draw from our theoretical model ( Figure 3) some important managerial implications, particularly for small business leaders in Thailand and possibly elsewhere in Asia who hope to improve their corporate sustainability by adopting the Sufficiency Economy philosophy. Based on the theoretical model, an example of sustainability management plan, as informed by Armenia et al [114], Markwick & Fill [115] and Zyznarska-Dworczak [116], is developed and demonstrated in Table 5 below. The plan contains objectives, responsible units, expected results and measures of success.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Moreover, there is also a need to extend the basics of accounting conceptualization to include organizational and social contexts [46][47][48]. Normative expectations are also directed to accounting education systems that would allow accountants to measure sustainable development results in a multifaceted way (e.g., [7,14,49]).…”
Section: Sustainability Accounting Development In the Light Of Accounmentioning
confidence: 99%
“…Sustainable change depends on the extent to which "integrated thinking" and "integrated accounting" can confront, challenge and colonize the "unintegrated thinking" and "unintegrated accounting" that dominates contemporary business [52,53]. Nevertheless, in scientific research there are studies concerning mainly individual aspects of accounting, such as reporting, attestation of disclosed results, cost accounting, environmental costing or assurance in the light of selected theories (e.g., [16,48,53,54]). There are few attempts to create a theoretical sustainability accounting framework promoting its holistic perception, and the existing ones have a very general nature (e.g., [7,10,11,55]).…”
Section: Sustainability Accounting Development In the Light Of Accounmentioning
confidence: 99%
“…In her research, Zyznarska-Dworczak focused on the relationship between managerial accounting and corporate social responsibility in the countries of Central and Eastern Europe with regard to the role of accounting in the broader social, ethical, environmental, cultural, and historical context. The observed changes in the companies of Central and Eastern European relate to the organisational structure; their production structure; management practices that take into account social, environmental and ethical expectations; performance measuring; the demand for more detailed information about their socioeconomic and environmental potential; the need for better skills and competence of accountants [30]. Further results from many studies have shown that companies with a socially responsible image achieve positive effects in relation to investors, find it easier to obtain finance, and achieve higher market capitalisation, because sustainable companies are considered less risky by investors.…”
Section: Corporate Social Responsibility (Csr)mentioning
confidence: 99%